A cross-sectional study to assess the knowledge, attitude and practice of contraceptive implants at tertiary care hospital in Ahmedabad, Gujarat - Vachhani, Smitul A.; Parikh, Tithi B.; Shah, Dhruvi H.; Shah, Dhruv S.; Vekariya, Nikhar P.; Vaishnav, Gunvant D.; Kapadia, Shital N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The aim of our study was to evaluate the knowledge, attitude and practice regarding contraceptive implants methods, the acceptance of implants and to find association between the various socio-demographic factors and the awareness about implants. Methods: A questionnaire based cross-sectional study was conducted among the female client coming to the Family Planning Out-Patient Department (OPD) of Obstetrics and Gynaecology department of a tertiary care-Medical college hospital in Ahmedabad. Sample size came out to be 200 based on time bound systemic sampling method. Results: Mean age of client is 27.14 years. Out of the 200 respondents, only 62.5% were aware about one of contraceptive method and about 17% had heard about contraceptive implants. 58% women believe that contraception should be used by every woman. 15% women felt that implants were safe and should be promoted. Only about 50 % (half) of the sample population used some form of contraception. 12 participants in our study used implants and 4 of them experienced irregular menstrual cycle. Religion, education and gravidity are significantly associated with the awareness of contraceptive implants. Conclusions: To conclude, significant improvement needs to be brought by Govt. of India and state Govt., in the awareness by information, education and communication (IEC material) and acceptance of contraception in general and implants in specific. Specific regional loopholes must be searched and identify and targeted to improve the overall acceptance and improving reproductive health of women.